The handbook of development communication and social change - Wilkins, Karin Gwinn, 1962-; Tufte, Thomas; Obregon, Rafael (2014)
"This Handbook of Development Communication and Social Change offers a valuable resource for advocates, scholars, and communities engaged in long-term and comprehensive struggles for social justice ... This book fills a critical niche by offering a comprehensive framework in a growing area of research and action, as social movements and organizations make strategic use of communication technologies and processes in a complex world of dominant global industries and oppressive political regimes ... This work integrates the interests of many of the International Association for Media and Communication Research (IAMCR) sections, including that of participatory communication, health communication, community communication, communication policy and technology, gender and communication, political communication, and political economy"--Introduction.
pt 1. Communicating development and social change -- pt 2. Developing strategic communication for social change -- pt 3. Activist approaches for development and social change.
Includes bibliographical references and index.
Keywords: Mass media -- Social aspects; Communication -- Social aspects; Communication in social action; Social change